CompTIA Advanced Security Practitioner (CASP) CAS-003 Cert Guide - Abernathy, Robin M.; McMillan, Troy (Pearson IT Certification, 2018)
Learn, prepare, and practice for CompTIA Advanced Security Practitioner (CASP) CAS-003 exam success with this CompTIA Approved Cert Guide from Pearson IT Certification, a leader in IT Certification learning and a CompTIA Authorized Platinum Partner. Master CompTIA Advanced Security Practitioner (CASP) CAS-003 exam topics Assess your knowledge with chapter-ending quizzes Review key concepts with exam preparation tasks Practice with unique sets of exam-realistic practice questions CompTIA Advanced Security Practitioner (CASP) CAS-003 Authorized Cert Guide is a best-of-breed exam study guide. Leading security certification training experts Robin Abernathy and Troy McMillan share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. The book presents you with an organized test preparation routine through the use of proven series elements and techniques. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. Review questions help you assess your knowledge, and a final preparation chapter guides you through tools and resources to help you craft your final study plan. The companion website contains the powerful Pearson Test Prep practice test software, complete with hundreds of exam-realistic questions. The assessment engine offers you a wealth of customization options and reporting features, laying out a complete assessment of your knowledge to help you focus your study where it is needed most. This online assessment engine enables you to access the practice tests via the Internet on any desktop, laptop, tablet, or smartphone device with internet connectivity. The web-based version also allows you to download the software to your desktop, so you can use the practice test even when you don't have an internet connection. The desktop version syncs with your online version when an internet connection is established, to update and track your progress. This integrated learning package offers these additional benefits: Allows you to focus on individual topic areas or take complete, timed exams; Presents unique sets of exam-realistic practice questions; Tracks your performance and provides feedback on a module-by-module basis.